(untitled) (ҚазҰУ Хабаршысы. Биология сериясы, 2017)
Моngolia besides fully supplying its population’s meat demand, it also has 30-40 thousand ton of meat reserve annually, other value added products of butchering, total of 100 million USD export products, also meat processing and exporting experiences [1]. Therefore guaranting pastoral Mongolian meat’s value, informing international market, improving value added meat and meat products export has important significance in Mongolian meat industry, stock raising and its veterinary development. Моngolia has enough meat reserve and its law, legal environment, state policy and strategy have been basically defined to support and develop meat market. Mongolian meat market analysis results have been united and completed in SWOT analysis, and some strategysuggestions have been promoted for value chain’s renewal.